2022
DOI: 10.3390/antiox11061139
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Free, Esterified and Insoluble-Bound Phenolic Antioxidants from Chickpeas Prevent Cytotoxicity in Human Hepatoma HuH-7 Cells Induced by Peroxyl Radicals

Abstract: Chickpeas are rich sources of bioactive compounds such as phenolic acids, flavonoids, and isoflavonoids. However, the contribution of insoluble-bound phenolics to their antioxidant properties remains unclear. Four varieties of chickpeas were evaluated for the presence of soluble (free and esterified) and insoluble-bound phenolics as well as their antiradical activity, reducing power and inhibition of peroxyl-induced cytotoxicity in human HuH-7 cells. In general, the insoluble-bound fraction showed a higher tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The separation was performed using the Eksigent Ekspert Ultra LC100 system with an LiChrospher 100 RP-18 column (125 mm × 4 mm i.d., 5 µm; Merck, Darmstadt, Germany) and an Ekspert Ultra LC100-XL autosampler. Both electrospray in the negative mode and chromatographic separation were carried out employing the conditions described by de Camargo et al [ 66 ]. The column temperature was maintained at 50 °C, the injection volume was 10 μL and a flow rate of 0.5 mL/min.…”
Section: Methodsmentioning
confidence: 99%
“…The separation was performed using the Eksigent Ekspert Ultra LC100 system with an LiChrospher 100 RP-18 column (125 mm × 4 mm i.d., 5 µm; Merck, Darmstadt, Germany) and an Ekspert Ultra LC100-XL autosampler. Both electrospray in the negative mode and chromatographic separation were carried out employing the conditions described by de Camargo et al [ 66 ]. The column temperature was maintained at 50 °C, the injection volume was 10 μL and a flow rate of 0.5 mL/min.…”
Section: Methodsmentioning
confidence: 99%
“…Phenols, essential bioactive compounds found in the chickpea seed coat ( Xu et al., 2007 ), include phenolic acids, flavonoids, and condensed tannins ( Singh et al., 2017 ; de Camargo et al., 2022 ), which offer various health benefits, including anti-carcinogenic, anti-thrombotic, anti-ulcer, anti-atherogenic, anti-allergenic, anti-inflammatory, antioxidant, and immune-modulating properties ( de Camargo et al., 2022 ; Begum et al., 2023 ). Total phenolic contents in chickpea range from 27.48–48.01 mg 100 g –1 for kabuli types, 38.59–83.52 mg 100 g –1 for desi types, and 63.08–113.30 mg 100 g –1 for wild species ( Kaur et al., 2019 ).…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…Total phenolic contents in chickpea range from 27.48–48.01 mg 100 g –1 for kabuli types, 38.59–83.52 mg 100 g –1 for desi types, and 63.08–113.30 mg 100 g –1 for wild species ( Kaur et al., 2019 ). They also observed that genotypes with higher phenol content exhibited greater antioxidant activity, suggesting a positive association between seed phenol content and antioxidant activity.A study using UPLC-MS/MS identified three specific phenolic acids in chickpea—taxifolin, biochanin, and m-hydroxybenzoic acid—that decrease oxidative damage in human HuH-7 cells induced by peroxy radicals, indicating hepatoprotective properties ( de Camargo et al., 2022 ).…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…Electrospray was used in negative mode. Chromatographic separation was carried out as published elsewhere [24].…”
Section: Determination Of Phenolics and Other Chemical Compoundsmentioning
confidence: 99%